An Integrated Approach to Coastal and Biological Observations - She, Jun; Muñiz Piniella, Ángel; Benedetti-Cecchi, Lisandro; Boehme, Lars; Boero, Ferdinando; Christensen, Asbjorn; Crowe, Tasman; Darecki, Miroslaw; Nogueira, Enrique; Gremare, Antoine; Hernandez, Francisco; Kouts, Tarmo; et al. (Frontiers in Marine Science, 2019)
Maritime economy, ecosystem-based management and climate change adaptation and mitigation raise emerging needs on coastal ocean and biological observations. Integrated ocean observing aims at optimizing sampling strategies and cost-efficiency, sharing data and best practices and maximizing the value of the observations for multiple purposes. Recently developed cost-effective, near real time technology such as gliders, radars, ferrybox and shallow water Argo floats, should be used operationally to generate operational coastal sea observations and analysis. Furthermore, value of disparate coastal ocean observations can be unlocked with multi-dimensional integration on fitness-for-the-purpose, parameter and instrumental. Integration of operational monitoring with offline monitoring programs, such as those for research, ecosystem-based management and commercial purposes, is necessary to fill the gaps. Such integration should lead to a system of networks which can deliver data for all kinds of purposes. Detailed integration activities are identified which should enhance the coastal ocean and biological observing capacity. Ultimately a program is required which integrates physical, biogeochemical and biological observation of the ocean, from coastal to deep-sea environments, bringing together global, regional and local observation efforts.